LEGAL ANALYSIS OF THE PALEMBANG RELIGIOUS COURT'S DECISION NUMBER: 39/PDT.P/2024/PA.PLG IN LIFE INSURANCE CLAIMS - Lia Desta Anggriani; Khalisah Hayatuddin; Sri Suatmiati (Universitas Labuhanbatu, 2025)
This study examines the legal implications of Palembang Religious Court Decision Number 39/Pdt.P/2024/PA.PLG on the legal standing of guardians of minors in submitting life insurance claims to PT Prudential Life Assurance. The research focuses on the role of religious court decisions in providing legal certainty for guardians acting on behalf of underage beneficiaries in insurance claim procedures. Using a normative juridical approach with a case-based analysis, this study analyzes statutory regulations, principles of Islamic family law, and judicial reasoning applied in the court’s decision. The findings indicate that the court’s ruling affirms the applicant’s status as the lawful guardian, thereby granting clear legal authority to represent the minor both in and outside judicial proceedings, including the submission of life insurance claims. This decision plays a significant role in bridging the gap between family law and insurance practice by ensuring legal certainty, protecting the rights of minors, and preventing administrative barriers in claim settlement processes. The study highlights the importance of judicial intervention by religious courts in resolving legal ambiguities related to guardianship and insurance claims, and underscores the broader contribution of such decisions to the development of legal certainty and justice in Islamic family law and life insurance practices in Indonesia.Keywords: legal analysis; religious court decision; guardianship of minors; life insurance claims